HUBUNGAN INTENSITAS MENGGUNAKAN MEDIA SOSIAL DAN PERSEPSI TERHADAP BAHASA NETLINGO DENGAN PERILAKU MENGGUNAKAN BAHASA NETLINGO - Virgian Aspara; Taufik Suprihartini (Interaksi Online, 2018)
Netlingo language today is increasingly prevalent used by active users of social media. Netlingo language which initially serves to streamline the delivery of a message has now changed the function as a language that is able to make conversations more interesting. This has an impact on the rarer use of standard Indonesian because it is displaced by the use of netlingo language. This study aims to explain whether there is a relationship between the three variables namely Intensity Using Social Media and Perception Against Netlingo Language with Behavior Using Netlingo Language. This study uses a quantitative approach and a paradigm of Positivism. By using sample purposive sampling type and number of respondents as much as 50 with criterion is active social media user of 13 - 20 years age range. The theory used in this research is Social Learning Theory for Intensity Relationship Using Social Media (X1) with Behavior Using Netlingo Language (Y) and Attribution Theory for the relationship between Perception on Netlingo Language (X2) and Behavior Using Netlingo Language (Y). The results of this study found that there is a significant relationship between the intensity of using social media with the behavior of using the language netlingo with a significance value of 0.00 with 100% confidence level. And there is a significant correlation between perception of netlingo language with behavior using netlingo language with significance value equal to 0.00 with 100% confidence level and correlation value of 0,571 which express strong relationship between intensity using social media with behavior using netlingo language then correlation value 0.457 which states a strong enough relationship between perception of netlingo language with behavior using netlingo language